COVID-19 and Labour Law: Canada - David J. Doorey (Italian Labour Law e-Journal, 2020)
Canadian governments have responded to COVID-19 in a number of ways. The federal government has responded primarily in the form of a massive stimulus package that includes: (1) the CanadianEmergency Response Benefit, which provides $500 per week to qualified workers who lose income due to COVID-19; and (2) the Canadian Emergency Wage Subsidyprogram, which covers up to 75 percent of wages for eligible private sector employers. The provinces have responded principally by introducing extended job protected leave entitlements to protect the jobs of employees forced to stop working due to COVID-19 related reasons.